Genome-Wide Analyses of Metal Responsive Genes in Caenorhabditis elegans - Aschner, Michael (Frontiers in Genetics, 2012)
Metals are major contaminants that influence human health. Many metals have physiologic roles, but excessive levels can be harmful. Advances in technology have made toxicogenomic analyses possible to characterize the effects of metal exposure on the entire genome. Much of what is known about cellular responses to metals has come from mammalian systems; however the use of non-mammalian species is gaining wider attention. Caenorhabditis elegans is a small round worm whose genome has been fully sequenced and its development from egg to adult is well characterized. It is an attractive model for high throughput screens due to its short lifespan, ease of genetic mutability, low cost, and high homology with humans. Research performed in C. elegans has led to insights in apoptosis, gene expression, and neurodegeneration, all of which can be altered by metal exposure. Additionally, by using worms one can potentially study mechanisms that underline differential responses to metals in nematodes and humans, allowing for identification of novel pathways and therapeutic targets. In this review, toxicogenomic studies performed in C. elegans exposed to various metals will be discussed, highlighting how this non-mammalian system can be utilized to study cellular processes and pathways induced by metals. Recent work focusing on neurodegeneration in Parkinson’s disease will be discussed as an example of the usefulness of genetic screens in C. elegans and the novel findings that can be produced.